Aesthetic Factors for High Value Chair Development - Rattanaphan, Salinee; Srichandr, Panya (Fine Arts Journal: Srinakharinwirot University, 2011)
This paper reports the findings of a research on factors influencing buying decisions of high value chairs and customer preference regarding forms, colors, and materials of the chairs. Interviews and questionnaire survey methodologies were employed. The result shows that ‘design’ is the most important factor influencing buying decisions. Quadrilateral shape with rounded edges is more favorable compared with other shapes. Slim design with balanced dimensions is more popular than thick, sturdy design. Light tone and fairly bright color is more preferable than darker ones. The majority of customers prefer the colors that are familiar to them. Wood is the most favorite structural material for the chairs while cotton is more popular than leather as a cover material. The implications of such findings for high value chair design and development are discussed.